International Court of Justice : digest of judgments and advisory opinions, canon and case law 1946-2012 (Vol. I) - Dahlhofff, Gunther; International Court of Justice (Leiden ; Boston : Martinus Nijhoff Publishers, 2012)
"This work offers ease of access to the ICJ's judgments and advisory opinions given between 25 March 1949 and 3 February 2012. It seeks to help scholars, practitioners and students of international public law to review the Court's jurisprudence for precedents in the Court's 'canon' and 'case law'. It allows the reader to read the judgments and opinions themselves, reduced to the unabbreviated and undistorted essence of the Court's reasoning. The work contains all the timeless elements of the Court's jurisprudence in this two-volume set, as well as a highly detailed index of the relevant terms and phrases of the judgments and advisory opinions"--Page 4 of cover.
Register of the judgments and advisory opinions of the International Court of Justice in the order of the case numbers of the Court's general list -- Register of the judgments and advisory opinions of the International Court of Justice by subject matter -- Digest of judgments and advisory opinions of the International Court of Justice -- Pronouncements of the International Court of Justice on customary international law.
Includes bibliographical references and index.
Keywords: International Court of Justice; International Court of Justice; International law -- Cases; CIJ = Cour internationale de justice; Jugements; Droit international; International law; Court decisions and opinions; Trials, litigation, etc; Court decisions and opinions